The Influence of Teacher Technology Ability, Parental Support, Teacher Competence, Learning Environment, and Learning Interest on Learning Outcomes with The Moderating Variable of Learning Motivation - Siti Kholifatun Sa’diah; Dedek Andrian; Nofriyandi Nofriyandi; Aulia Sthephani; Editha Dacara (Yayasan Keluarga Guru Mandiri, 2025)
In digital era, motivation become the best variable to increase student learning outcome. This research aims to examine the influence of teachers' technological abilities, parental support, teacher competence, learning environment, interest in learning on learning outcomes with the moderating variable learning motivation of junior high school students in Riau province. The population in this study were all junior high school students in Pekanbaru were taken randomly using a simple random sampling technique, the number of samples taken was based on 9 schools using the Slovin formula, so that 270 students were obtained from the 9 schools. The data collection technique used was a survey and the instrument was a closed questionnaire. The data analysis used in this research is descriptive testing, mediation testing, and hypothesis testing. Based on the results of the t test in the table statistics, it can be seen that there is no influence of teacher technology abilities, teacher competence and interest in learning on learning outcomes. Parental support and the learning environment have a significant effect on learning outcomes. Learning motivation is only able to moderate the variables of teacher technology ability, parental support, teacher competence on learning outcomes.